Acute Painful Transfusion Reactions (APTRs): A Comprehensive Review of Clinical Features, Pathophysiology, Diagnosis, and Management - Sophia Delicou; Aspasia Argyrou; Sophia Mellou; Aikaterini Xydaki; Anthippi Gafou; Constantina Politis (Thalassemia Reports)
It is important to recognize the significance of acute painful transfusion reactions (APTRs) as a complication of blood transfusions. These adverse reactions are characterized by the onset of acute pain after the administration of blood components. Despite their potential to cause significant discomfort and distress to patients, these reactions are frequently disregarded and under-reported in clinical practice. This review aims to provide a comprehensive analysis of the clinical features, pathophysiology, diagnosis, incidence, and management of APTRs, emphasizing the necessity for heightened awareness and further research in this field.